2010
DOI: 10.1016/j.envres.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of developmental polychlorinated biphenyl (PCB) exposure in relation to post-vaccination antibody response at 6-months of age

Abstract: Background-Extensive experimental data in animals indicate that exposure to polychlorinated biphenyls (PCBs) during pregnancy leads to changes in offspring immune function during the postnatal period. Whether developmental PCB exposure influences immunologic development in humans has received little study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…PCB concentrations were determined in the National Reference Laboratory for Dioxins and Related Compounds for the Slovak Republic, at the Slovak Medical University in Bratislava. Descriptive data for PCB concentrations in maternal, cord, and infant serum were reported previously by Jusko et al (2010;. The PCB levels in maternal blood in Michalovce were ≈ 2-fold higher than in mothers in Svidnik.…”
Section: Study Areamentioning
confidence: 99%
“…PCB concentrations were determined in the National Reference Laboratory for Dioxins and Related Compounds for the Slovak Republic, at the Slovak Medical University in Bratislava. Descriptive data for PCB concentrations in maternal, cord, and infant serum were reported previously by Jusko et al (2010;. The PCB levels in maternal blood in Michalovce were ≈ 2-fold higher than in mothers in Svidnik.…”
Section: Study Areamentioning
confidence: 99%
“…The future evaluation of non-POP substances (e.g., heavy metals) may confirm or refute their potential confounding effects on different type of cell populations in children from a heavily PCB polluted area. Jusko et al (2010) observed little evidence for an association between PCB exposures measured during the pre-natal and early post-natal period and post-vaccination specific antibody responses to anti-haemophilus influenzae Type b, tetanus toxoid, and diphtheria toxoid at 6-months-of-age in the same population of Michalovce and Svidnik/Stropkov districts. In addition, in utero and early post-natal PCB exposures are not associated with total serum immunoglobulin levels (IgG, IgA, IgM, or IgE) in infants at 6-months-of-age, regardless of the timing of PCB exposure (Jusko et al, 2011).…”
Section: Journal Of Immunotoxicologymentioning
confidence: 71%
“…The mean maternal serum levels of the sum of six PCBs (∑ PCB ) were 7.5 and (718.5 ng/g lipid) in Michalovce and 3.6 ng/ml (373.7 ng/g lipid) in Svidnik/Stropkov (Sonneborn et al, 2008). Descriptive data for the PCB concentrations in maternal, cord, and infant serum was reported previously (Jusko et al, 2010(Jusko et al, , 2011 …”
Section: Study Area and Populationmentioning
confidence: 99%
“…The extent of pollution can be illustrated by comparing the median serum concentration for the same time period in 1009 adult subjects for congener PCB 153 of 578 ng/g of lipid in the Michalovce district (Petrik et al, 2006) with the median serum concentration in 415 nonpregnant women for congener PCB 153 of 8.3 ng/g of lipid in USA (Woodruff et al, 2011). The characteristics of infants and mothers participating in the study were described earlier (Jusko et al, 2012; Jusko et al, 2011; Jusko et al, 2010; Park et al, 2010; Sonneborn et al, 2008a, 2008b). The study protocol was approved by Institutional Review Boards at the University of California, Davis and the Slovak Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…In the currently used former option we describe dependence of the concentration of PCB 153 in serum of 305 breastfed infants on length of breastfeeding. Although we determined the concentrations of 15 PCB congeners in serum specimens, we focused our analyses on PCB-153 for two reasons: 1) PCB-153 is highly correlated with total PCB concentration in this cohort (Jusko et al, 2010), and 2) it was detectable in the vast majority of child specimens (Kocan et al, 2004). …”
Section: Introductionmentioning
confidence: 99%